Analysis of Speaking Skills in Speech of Grade VI Students: A Case Study of Pedurungan Kidul 02 Semarang Elementary School - Causarina, Princesa Vitara; Ahmadi, Farid (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
Everyone can make a speech, but not everyone can make a good and correct speech. Everyone needs to develop speaking skills in everyday life. Therefore, this research aims to describe the speaking skills of class VI students: a case study of SD Pedurungan Kidul 02 Semarang.This research was conducted at SD Negeri Pedurungan Kidul 02, Semarang City, Central Java. The data collected are qualitative in the form of narratives regarding the ability of speaking skills in delivering speeches, factors that influence speaking skills, and efforts to improve speaking skills in delivering opinions. The data sources used were primary data and secondary data. The data collection techniques used were observation, interview, test, and documentation. The results of this research are that the speaking skills of the three class VI students at SD Negeri Pedurungan Kidul 02 Semarang City are categorized as